Developing A Framework: Adoption of International Financial Reporting Standards (IFRS) and Its Implications on Organizational Performance - Mohammed Alshamsi, Khuloud Humaid Saeed; Ahmad, Ahmad Nur Aizat (International Journal of Sustainable Construction Engineering and Technology, 2024)
This study was aimed to develop a framework for adopting International Financial Reporting Standards (IFRS) and gauging its influence on Organizational Performance. The developed framework reveals that Organizational factors strongly align with Financial Reporting & Transparency and Economic & Industry Impact & Global Market Presence but not with Decision-Making & Governance. however, the accounting capabilities factors are predominantly linked to industry impact & global market presence, while top management support factors robustly connect with both industry impact & global market presence and subsequently, decision-making & governance. Conversely, readiness factors exhibit a compelling relationship across financial reporting & transparency, industry impact & global market presence, and decision-making & governance, highlighting their significant impact on organizational performance. This framework can be applicable in organizational contexts, providing guidance for strategic decision-making and performance enhancement in the adoption of IFRS. Leveraging the identified correlations, organizations can focus on strengthening specific factors, including Organizational Readiness, accounting capabilities, Top management support, and Readiness, to enhance financial reporting, transparency, industry impact, global market presence, and decision-making processes. Implementing targeted strategies based on these relationships may contribute to overall organizational success and sustainable growth.